Synthesis and lipid-lowering effects of phospholipid-polyunsaturated fatty acids (PL-PUFA) in high fat diet induced obese mice. (4th March 2023) - Fang, Hua; Li, Mengyu; Jin, Wenhui; Zhang, Yiping; Hong, Zhuan; Chen, Weizhu
Abstract: In this study, phospholipid-polyunsaturated fatty acids (PL-PUFA), which was a glycerophosphamide analogue containing DHA/DPA of phospholipid derivative, was synthesized from algae oil in two steps. The compound of P1 /P2 in the PL-PUFA was isolated through preparative HPLC with the contained of 70.24%, and 23.86%, respectively. Intragastric administration of 200 mg/kg PL-PUFA can strongly suppress net body weight gain and obesity-related hyperlipidemia. The net body-weight gain of treatment group was decreased 5.18% than that of the normal group. Serum TC levels of treatment group were significantly suppressed, and it was reduced by 55.95%. However, for HDL-C levels, none of the model group and treatment group showed significant differences comparing with the normal group. The preliminary biological data of PL-PUFA in this work strongly supports our belief that the analogue glycerophosphamide structure containing with ω-3 PUFAs is providing a beneficial effect on lowering serum lipids and TGs. Graphical Abstract: UF0001